Efficacy and safety of perampanel in adolescent patients with drug-resistant partial seizures in three double-blind, placebo-controlled, phase III randomized clinical studies and a combined extension study. (July 2015) - Rosenfeld, William; Conry, Joan; Lagae, Lieven; Rozentals, Guntis; Yang, Haichen; Fain, Randi; Williams, Betsy; Kumar, Dinesh; Zhu, Jin; Laurenza, Antonio
Abstract Objective Assess perampanel's efficacy and safety as adjunctive therapy in adolescents (ages 12–17) with drug-resistant partial seizures. Methods Adolescent patients enrolled in multinational, double-blind, placebo-controlled, phase III core studies (studies 304, 305, or 306) completed 19-week, double-blind phase (6-week titration/13-week maintenance) with once-daily perampanel or placebo. Upon completion, patients were eligible for the extension (study 307), beginning with 16-week, blinded conversion, during which placebo patients switched to perampanel. Patients then entered the open-label treatment. Results Of 1480 patients from the core studies, 143 were adolescents. Pooled adolescent data from these core studies demonstrated median percent decreases in seizure frequency for perampanel 8 mg (34.8%) and 12 mg (35.6%) were approximately twice that of placebo (18.0%). Responder rates increased with perampanel 8 mg (40.9%) and 12 mg (45.0%) versus placebo (22.2%). Adolescents receiving concomitant enzyme-inducing antiepileptic drugs (AEDs) had smaller reductions in seizure frequency (8 mg:31.6%; 12 mg:26.8%) than those taking non-inducing AEDs (8 mg:54.6%; 12 mg:52.7%). Relative to pre-perampanel baseline, seizure frequency and responder rates during the extension (Weeks 1–52) improved with perampanel. Most commonly reported adverse events in adolescents during the core studies were dizziness (20.4%), somnolence (15.3%), aggression (8.2%), decreased appetite (6.1%), and rhinitis (5.1%). Dizziness (13.2%), somnolence (11.6%), and aggression (6.6%) most often led to perampanel interruption/dose adjustment during the extension. Significance Data demonstrated adjunctive perampanel treatment in adolescents with drug-resistant partial seizures produced better seizure control versus placebo, sustained seizure frequency improvements, and a generally favorable safety profile. Results were comparable to the overall study population. Clinical Trial Registration: clinicaltrials.gov Identifiers: Study 304: NCT00699972; 305: NCT00699582; 306: NCT00700310; Study 307: NCT00735397.